Hylin-a1: A Host Defense Peptide with Antibacterial Potential against Staphylococcus aureus Multi-Resistant Strains - Annalisa Chianese; Carla Zannella; Francesco Foglia; Bianca Maria Nastri; Alessandra Monti; Nunzianna Doti; Gianluigi Franci; Anna De Filippis; Massimiliano Galdiero (MDPI AG, 2023)
In recent years, the resistance of pathogenic microorganisms to common antimicrobial agents has raised to a severe public health problem. The moderate and wise use of antimicrobials and the prevention of infections are the most effective strategies for decreasing the spread and development of resistance. Therefore, the World Health Organization (WHO) has intensified the search for new drugs to fight emerging pathogens. Antimicrobial peptides (AMPs), also known as host defense peptides (HDPs), play a crucial role in innate immunity, representing one of the first line of defense against microbial attacks. In this study, we evaluated the antibacterial activity of the AMP named Hylin-a1 (derived from the skin of the frog Heleioporus albopunctatus) against Staphylococcus aureus strains. S. aureus represents a commensal bacterium but also the principal causative agent of several human infections, including bacteremia, endocarditis, skin and device-related infections. Hylin-a1 toxicity was evaluated on human keratinocytes; once the non-cytotoxic concentration range was determined, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were analyzed, and time-killing assays were performed to verify the bacteriostatic and/or bactericidal activity of the peptide. We found that Hylin-a1 exerted a bacteriostatic action against most of the tested strains, with 90% inhibition at the concentration of 6.25 μM. Noteworthy, the peptide at a very low concentration (~3 μM) significantly blocked the growth of β-lactam- and methicillin-resistant S. aureus. The levels of interleukin (IL)-1β, IL-6 and IL-8 were quantified through a molecular assay, indicating that the peptide was able also to regulate the inflammatory response following bacterial infection. The effect of Hylin-a1 on S. aureus cell morphology was also evaluated. Altogether, these results indicate the high therapeutic potential of Hylin-a1 against a wide variety of clinical manifestations caused by S. aureus.